Surgical treatment of pulmonary tuberculosis in children - M. S. Opanasenko; O. V. Tereshkovych; M. Yu. Shamray; B. M. Konik; L. I. Levanda; M. I. Kalenichenko; S. M. Shalahai; O. K. Obremska (Клінічна хірургія, 2019)
Objective. To estimate the results of surgical treatment in children, suffering pulmonary tuberculosis.